The Use of History Textbooks as Learning Resource For Students of The History Education Study Program at UISU - Mestari Zai; Surya Aymanda Nababan; Pulung Sumantri; Abdul Azis (Universitas Islam Sumatera Utara, 2023)
Learning resources are part of learning that is very important for the success or failure of learning. So far, experience has shown that many lecturers who teach on campus still rely on books as the main reference in their teaching process. Of course, this cannot be called wrong, but making textbooks the only reference work has led to a decrease in the creativity of lecturers and students. This also happened to history subjects at UISU. In sixth semester history classes, where the subject is based mostly on facts and past events and one's memory is limited, books are very reliable in recalling the lecturer's memory of the material he taught the students. Likewise, students who are often given assignments by subject lecturers often make history textbooks and/or textbooks for other subjects, most of them make textbooks as learning resources and sources or materials to complete their subject assignments. The purpose of this work is to describe and analyze the use of history textbooks as a source of student learning in the history curriculum of the Islamic University of North Sumatra. The research method used in the preparation of this article is the literature review method, namely by means of sources obtained from books and scientific journals. The results of this study indicate that history textbooks play a very important role in ongoing history learning, so that it can be said that textbooks must have several content qualifications, which include the completeness of the material, the breadth and depth of the material. about the material and the accuracy of the material. Textbooks also have advantages and disadvantages, such as textbooks which must contain core and basic skills to support successful learning.